ETHNOMATHEMATICAL EXPLORATION OF THE KABANJAHE GRAND MOSQUE BUILDING, KARO REGENCY - Desmi Fitri Syahdani Br Sitepu; Tanti Jumaisyaroh Siregar (Pena Cendekia Insani, 2025)
This study explores the ethnomathematical elements in the architecture of the Kabanjahe Grand Mosque. Using a qualitative descriptive approach with an ethnographic lens, data was collected through observation, interviews, and visual documentation. The findings reveal that the mosque’s architecture incorporates geometric shapes, such as squares, rectangles, triangles, and circles, which reflect both mathematical and cultural significance. These elements demonstrate how mathematics can be integrated into local culture and used as a teaching resource. The research highlights the value of ethnomathematics in educational contexts, reinforcing the importance of incorporating cultural elements into mathematics learning.